Advertising Exposure, Word of Mouth, and Generation Z Consumer Loyalty in Online Marketplace: The Mediating Influence of Brand Awareness - Novel Reonald; Dian Irma Aprianti (Khazanah Sosial, 2024)
This study investigates the influence of advertising exposure and word of mouth (WOM) on Generation Z consumer loyalty, examining the mediating role of brand awareness in the context of online purchases on marketplace platforms. We employed a quantitative descriptive approach, gathering primary data through questionnaires and observations of Generation Z consumers who have made at least two purchases on Shopee. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the aid of the WarpPLS 7.0 software. The findings reveal that both advertising exposure and WOM significantly enhance brand awareness. Additionally, each has a direct and positive impact on consumer loyalty. However, the influence of advertising exposure and WOM on consumer loyalty does not necessarily require the mediation of brand awareness. These results suggest that Shopee’s robust advertising campaigns and effective WOM communications significantly embed the brand within the consumer's psyche, facilitating easy recall of Shopee as a platform known for attractive promotions. In conclusion, the formation of consumer loyalty can occur directly through advertising exposure and WOM, highlighting their pivotal roles in cultivating enduring consumer loyalty to Shopee.